Arteries of the basis of the encephalon in dogs (Canis familiar is, Linnaeus, 1758). II. Formation and behaviour of the encephalon arterial circuit - Alcântara, Maria Aparecida de; Prada, Irvênia Luiza de Santis (Brazilian Journal of Veterinary Research and Animal Science, 1996)
For this research, 30 pieces of crossbed dogs were dissected, in order to improve our knowledge on the behaviour of the arteries in the basis of the encephalon. The preparations showed that the peculiar disposal of the terminal branches of the internal carotid, and the terminal branches of the basilar artery determine, starting from the splitting of the internal carotid artery - in both sides - into rostral and caudal terminal branches, this formation invariably displays the shape of a small arc, or that of ahorseshoe with caudal concavity. Caudally, it forms, in variable ways, pyriform (56,6%) or poligonal (43,3%) pictures, a) rostrally represented by left and right rostral cerebral arteries; b) laterally, by the rostral and caudal branches of left and right internal carotid arteries; c) caudolaterally, by left and right terminal branches of the basilar artery.